Fast Sam, Cool Clyde, and Stuff - Myers, Walter Dean. (New York : Puffin, 1988)
New to 116th street in New York, a young boy soon makes friends and begins a year of unusual experiences.
6.0
Young Adult
Young Adult.
Notable/Best Books (A.L.A.)
School Library Journal
Booklist
Keywords: City and town life -- Fiction; City and town life -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction